2010
DOI: 10.1111/j.1528-1167.2009.02482.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the anticonvulsant efficacy of sodium channel inhibitors by an NK1‐receptor antagonist in the rat

Abstract: SUMMARYPurpose: Many patients with epilepsy are refractory to anticonvulsant drugs or do not tolerate side effects associated with the high doses required to fully prevent seizures. Antagonists of neurokinin-1 (NK1) receptors have the potential to reduce seizure severity, although this potential has not been fully explored in animals or humans. The present study was designed to evaluate the efficacy of the NK1-receptor antagonist, vofopitant, alone and in combination with different anticonvulsant drugs. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Moreover, at the doses tested vofopitant did not produce CNS side effects, and it did not enhance side effects induced by high doses of lamotrigine. Analysis of the dose-effect relationship for GR-205,171 indicated that a high ([99 %) occupancy of NK-1 receptors is required for an effect to be observed, consistent with previous behavioral and human clinical studies with this pharmacologic class (Kalinichev et al 2010). The authors concluded that in patients with refractory epilepsy some benefit could be derived from adding treatment with a suitable NK-1 receptor antagonist to treatment with a sodium channel blocker.…”
Section: Seizurementioning
confidence: 57%
See 2 more Smart Citations
“…Moreover, at the doses tested vofopitant did not produce CNS side effects, and it did not enhance side effects induced by high doses of lamotrigine. Analysis of the dose-effect relationship for GR-205,171 indicated that a high ([99 %) occupancy of NK-1 receptors is required for an effect to be observed, consistent with previous behavioral and human clinical studies with this pharmacologic class (Kalinichev et al 2010). The authors concluded that in patients with refractory epilepsy some benefit could be derived from adding treatment with a suitable NK-1 receptor antagonist to treatment with a sodium channel blocker.…”
Section: Seizurementioning
confidence: 57%
“…The authors found that vofopitant had no anticonvulsant efficacy by itself, but could enhance the anticonvulsant efficacy of lamotrigine and other sodium channel blockers. This effect was mediated by NK-1 receptors (Kalinichev et al 2010). Moreover, at the doses tested vofopitant did not produce CNS side effects, and it did not enhance side effects induced by high doses of lamotrigine.…”
Section: Seizurementioning
confidence: 97%
See 1 more Smart Citation
“…NK-1 receptor antagonists have been tested in animal models of epilepsy and were found effective. CP-122,721-1, attenuated kainate induced seizure activity [180] while GR205171 potentiated the anticonvulsant efficacy of sodium channel inhibitors [181]. Thus, research using NK-1 receptor antagonist in epilepsy is expected to intensify in the future [182].…”
Section: Substance Pmentioning
confidence: 99%
“…A recent study reported that aprepitant can decrease neuronal cell death and oxidative stress in bilateral common carotid artery-occluded rats [ 90 ]. Interestingly, GR205171 (vofopitant), a NK-1R antagonist, demonstrated potent antiepileptic effects as a Na + channel blocker, rather than exerting direct antiepileptic efficacy [ 91 ]. Thus, NK-1R antagonists may elicit synergistic effects with other traditional AEDs, which could be a promising target for treatment of refractory epilepsy.…”
Section: Introductionmentioning
confidence: 99%